The trouble with reporting and utilization of workplace violence data in health care. (18th October 2018) - Morphet, Julia; Griffiths, Debra; Innes, Kelli
Abstract: Aim: The study aimed to evaluate the reporting, monitoring and use of workplace violence data in Victorian health services. Background: Surveillance of workplace violence is important in understanding the circumstances in which workplace violence occurs and development of relevant and appropriate prevention and intervention strategies. Method: A descriptive exploratory approach was used. Fifteen staff from occupational health and safety, quality and safety, and nurse unit managers, from five major metropolitan health services were interviewed. Recorded interviews were transcribed verbatim and thematically analysed. Results: Three themes were identified: (a) "under‐reporting of workplace violence, " (b) "inconsistent guidance" caused subjective and variable data coding and (c) "application of data" described how health services used the data available to them, to inform the development and implementation of systems designed to prevent workplace violence. Conclusions: Improved reporting systems may increase consistency in reporting, enable data sharing across organisations and assist in planning of prevention strategies. Implications for nursing management: Staff should be encouraged to complete incident reports for each episode of workplace violence. Incident reporting systems must be simplified to reduce the burden of reporting. Nurse managers should advocate for the sharing of health service workplace violence data, to enable improved prevention across all services.